Political Brand Equity Model: The Integration of Political Brands in Voter Choice. Issue 2 (3rd April 2017) - Ahmed, Mirza Ashfaq; Lodhi, Suleman Aziz; Ahmad, Zahoor
Abstract : The voters' choices about political parties have many similarities with how they make their choices about commercial brands. Therefore, political parties are now constantly applying the concept and strategies of brand management to make the political product attractive, appealable, trustable, differentiable, a source of long-term relationships, and a decision-making driver. Furthermore, the political parties have to play an active role in the community's political socialization processes, which rely heavily on branding strategies. Because, the party equity is largely based on the community's social gregariousness that has profound effect on the electorates' propensity to participate in the politics. This study has deeply explored and broadened the concept of party equity analogous to commercial brand equity typology by developing a politics-specific brand equity model. This model demonstrates the integration of political brands in voter choice. Empirically, this model has been validated by collecting 550 valid responses from the constituency of District Gujrat, Pakistan. A careful analysis of these responses through structural equation modeling methodology has revealed that political parties vary according to the outcomes of their role in the political socialization process of the communities, loyalty, and voters' attitude. Parties that have favorable role in the socialization process have strong party knowledge and thus have high party equity as compared to competing political parties, which have a weak position of party knowledge. Similarly, this study provides the roadmap and guidelines for the political parties to manage their party equity. Similarly, the model would be able to facilitate political parties in comparing different constituencies on the basis of their diversified social dynamics and political knowledge and in the development of a constituency-based manifesto, also termed "localized manifesto, " to further enhance their vote bank.